Does the Serum Vaspin Level Have a Role in the Diagnosis of Primary Ovarian Insufficiency? - Fatma Nur Koyun; Nafiye Yilmaz; Duygu Tugrul Ersak (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: This study was designed to compare the serum vaspin levels between patients with primary ovarian insufficiency (POI) and healthy fertile women.